The Zebrafish Annexin Gene Family - Farber, Steven A.; De Rose, Robert A.; Olson, Eric S.; Halpern, Marnie E. (Genome Research, 2003)
The Annexins (ANXs) are a family of calcium- and phospholipid-binding proteins that have been implicated in many cellular processes, including channel formation, membrane fusion, vesicle transport, and regulation of phospholipase A2 activity. As a first step toward understanding in vivo function, we have cloned 11 zebrafish anx genes. Four genes (anx1a, anx2a, anx5,and anx11a) were identified by screening a zebrafish cDNA library with a Xenopus anx2 fragment. For these genes, full-length cDNA sequences were used to cluster 212 EST sequences generated by the Zebrafish Genome Resources Project. The EST analysis revealed seven additional anx genes that were subsequently cloned. The genetic map positions of all 11 genes were determined by using a zebrafish radiation hybrid panel. Sequence and syntenic relationships between zebrafish and human genes indicate that the 11 genes represent orthologs of human anx1,2,4,5,6,11,13,and suggest that several zebrafish anx genes resulted from duplications that arose after divergence of the zebrafish and mammalian genomes. Zebrafish anx genes are expressed in a wide range of tissues during embryonic and larval stages. Analysis of the expression patterns of duplicated genes revealed both redundancy and divergence, with the most similar genes having almost identical tissue-specific patterns of expression and with less similar duplicates showing no overlap. The differences in gene expression of recently duplicated anx genes could explain why highly related paralogs were maintained in the genome and did not rapidly become pseudogenes.